Improving the quality of health care through practice guidelines: to what extent systematic reviews support health policy? (Italian Journal of Public Health, 2006)
Background: The evidence-based medicine movement has extended its influence to other fields. In the areaof quality improvement, the evidence-based approach stimulated the diffusion of practice guidelines as arelevant policy tool. Concurrently guidelines have become the object of a large body of research, includingsystematic reviews.Objective: To explore to what extent systematic reviews on guideline implementation strategies supporthealth policy decisions in this area.Methods: The use of systematic reviews in terms of influencing decisions concerning quality of care will beexamined by focusing, in particular on two dimensions – guidelines as policy tools and guidelines as anobject of research - and finally to what extent these two dimensions match.Results/Discussion: We highlight three aspects of mismatching between research and policy: thecharacteristics of guidelines, the relationship between guideline development and implementation and thetype of research question addressed. These aspects represent conceptual obstacles that further challengethe adoption of an evidence based approach and limit the use of systematic reviews in supporting policydecisions in the area of quality improvement
Keywords: evidence based policy; systematic review; quality improvemen; practice guidelines